nacl溶液中co2置换ch4水合物的分子动力学模拟 - 周雪冰; 易莉芝; 梁德青 (2016)
The process of methane hydrate replacement with carbon dioxide in aqueous NaCl solutions is investigated using molecule dynamics simulation.The results show that at the beginning of the simulations,the cages near the hydrate/solution interface distort in